Dash & Lily's book of dares - Cohn, Rachel; Levithan, David (New York Alfred A. Knopf, 2010)
Told in the alternating voices of Dash and Lily, two sixteen-year-olds carry on a wintry scavenger hunt at Christmas-time in New York, neither knowing quite what--or who--they will find.
KAL- 3945, donated by Jowana B. Bueser.
Keywords: Treasure hunt (Game) -- Fiction; Identity -- Fiction; New York (N.Y.) -- Fiction